A Historical Analysis of Media Reportage on the Sikh Genocide of 1984: Implications for National Security of the Indian State - Choudry, Anup Singh; Isabirye, Joel; Mbabazize, Mbabazi; Olusola, Ojo (Technium Social Sciences Journal, 2022)
This study critically examined the media reportage on the Sikh genocide of 1984. From the reports, the study drew inferences on the effect of the Sikh genocide on India’s national security within the spectrum of the persistent agitation for self-determination by the Sikh people of Punjab. Despite the devastating implications of the crisis for India security architecture, much that is quite revealing has not been captured in extant body of literature on the subject of the Sikh genocide. This lacuna informs one of the major motivations for this treatise. Two main research questions were critical to this analysis: What was the effect of the Sikh genocide on the desire for self-determination of the Punjab people? What were the implications of the Sikh genocide of 1984 for the security architecture of the Indian State? To answer these questions, a content analysis of media reports on the subject matter was used as the primary method of data collection which was complemented by in-depth interviews of key stakeholders. Findings revealed that Sikh genocide of 1984 was the major catalyst for the call for self-determination and the resultant crisis that have erupted in the region since then. It was further revealed that the Sikh genocide of 1984 had negatively impacted on the security of lives and also on the perception of security by people in India and the Punjab state in particular. The study concluded that there is need for a permanent and acceptable solution to the issue of self-determination and mutual distrust in the Punjab State in the interest India’s national security. It was recommended that a community based approach hinged on the principles of compromise and inclusiveness should be adopted towards resolving the crisis in the region.